Exploiting the Imidazolium Effect in Base‐free Ammonium Enolate Generation: Synthetic and Mechanistic Studies. Issue 46 (20th October 2016) - Young, Claire M.; Stark, Daniel G.; West, Thomas H.; Taylor, James E.; Smith, Andrew D.
Abstract: N‐Acyl imidazoles and catalytic isothiourea hydrochloride salts function as ammonium enolate precursors in the absence of base. Enantioselective Michael addition–cyclization reactions using different α, β‐unsaturated Michael acceptors have been performed to form dihydropyranones and dihydropyridinones with high stereoselectivity. Detailed mechanistic studies using RPKA have revealed the importance of the "imidazolium" effect in ammonium enolate formation and have highlighted key differences with traditional base‐mediated processes. Abstract : Drop the Base : N ‐Acyl imidazoles act as ammonium enolate precursors in the presence of catalytic isothiourea hydrochloride salts in the absence of base. Subsequent reactions with various Michael acceptors proceed with high stereoselectivity. Mechanistic investigations revealed the importance of the "imidazolium effect" during enolate formation and highlight key differences with traditional base‐mediated processes.